A new clavarioid wood-inhabiting fungus, Artomyces tsugae (Russulales Basidiomycota), from Guangxi, southern China - Zhao, Ya-Lin; Li, Ming-Rui; Zhaung, Lei; Cai, Qing; Dai, Yu-Cheng (Phytotaxa, 2026)
A new lignicolous species, Artomyces tsugae, is described from the high mountains of Guangxi, subtropical China, based on morphological examination and phylogenetic analysis. The new species is characterized by annual, stipitate, well-branched and snow white basidomata when fresh, a monomitic hyphal system with clamp connections on generative hyphae, the presence of gloeoplerous hyphae and gloeocystidia, ellipsoid, hyaline, thin-walled, verrucose, amyloid basidiospores measuring 4.6–5.2 × 3.1–3.6 µm, and growing on rotten wood of Tsuga tchekiangensis. Phylogenetic analysis based on ITS sequences indicated that it was closely related to A. brunneoalbus, A. yunnanensis, and five other species. A description, illustrations, and phylogenetic analysis results of the new species are provided. In addition, the new species is compared with closely related and similar species.